Ondansetron versus granisetron in the prevention of chemotherapy induced nausea and vomiting in children with acute lymphoblastic leukemia. - Siddique, R; Hafiz, MG; Rokeya, B; Jamal, CY; Islam, A (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):680-8 The abstract of this article is available on the PubMed website